Study of improving the sports achievements of students in Surakarta City - Hercules Sianipar; Mohammad Arif Ali; Nanda Adi Nugroho; Syahrul Habib Maulana (Sriwijaya Journal of Sport, 2024)
Athletes' achievements are the result of their abilities and efforts in attaining good performance. Guidance from coaches plays a role in achieving such success. The quality of athletes is a key factor in their success. Regional Student Sports Week serves as a platform for developing and nurturing potential student athletes. The city of Surakarta has experienced an increase in athletic achievements each year. The success of athletes is influenced by factors such as the quality of athletes, the qualifications and intensity of coaches, training programs and schedules, as well as competitions and available facilities. This study explains the importance of athletic achievements and the factors that influence them, including athlete development, social support, and regulatory systems. The research focuses on the Regional Student Sports Week in Surakarta as a venue for developing student athletes at the provincial and national levels. The study adopts a descriptive approach, utilizing data on student athletic achievements by the Youth and Sports Services Surakarta City. The analysis reveals that Youth and Sports Services conducts selective recruitment of athletes, implements the Special Sports Class program, and collaborates with sports teachers. Licensed or certified coaches are essential in athlete development. The success of Regional Student Sports Week athletes in Surakarta is supported by quality facilities, incentives, and rewards. Adequate facilities are vital resources in the development of athletes in Surakarta, and their management should be improved in accordance with national standards.